Impact of information technology on productivity and efficiency in Iranian manufacturing industries - Amir Gholam Abri; Mahmoud Mahmoudzadeh (Journal of Industrial Engineering International, 2015)
The aim of this paper is to assess the impact of information technology (IT) on the productivity and efficiency of manufacturing industries in Iran. So, the data will be collected from 23 Iranian manufacturing industries during ''2002-2006'' and the methods such as DEA and panel data used to study the subject. Results obtained by the above two methods represent that IT has a positive and statistically significant effect on the productivity of manufacturing industries. It will be more in high IT-intensive industries than the other industries. But, there is no significant difference between the growth of labor productivity in IT-producing and IT-using industries.
Keywords: 650; Information technologies (IT); Efficiency; Data envelopment analysis (DEA); Panel data; Productivity; Malmquist Productivity Index (MPI)